'So do you hear me? And "how" do you hear me?' Perceptions of lecturers on students from Portuguese-speaking African countries in Portuguese higher education - Matias, Ana Raquel Monteiro (Language and intercultural communication, 2024)
The internationalisation of Portuguese higher education implies multicultural challenges arising from the Portuguese language variation. Nevertheless, the perceptions of lecturers about their students are rarely analysed, though influencing learning. This will be the focus of our article, using focus groups. Findings show that lecturers experience unexpected situations of incomprehension with students speaking varieties of Portuguese, while profiling differently students' sociolinguistic characteristics. Thirdly, participants differ on strategies applied to overcome difficulties encountered, such as pedagogical and monitoring. Our conclusions highlight the need to deconstruct lecturers' ideologies as listening subjects of Portuguese language varieties and its socialisation, designing solutions promoting their capacity-building.